Implementation of a Location Services Based Android Application and Accompanying Server Backend - Lukaček, Kristijan (Array, 2021)
This paper is focused on the usage of location services in mobile applications that were developed for the purpose of reporting different events that are based on their location. The event that is intended to be generic and universal can, as in examples used in this paper, be the reporting of some occurrence to a city"s communal affairs office. Such a generic event can include both multimedia and textual data, in addition to location information obtained using mobile device running the app. The software solution that is described in this paper consists of a mobile application that was developed for the Android operating system and a web application that includes a series of PHP scripts that run on a dedicated server. The web application consists of a backend scripts that facilitate the communication of a smart phone and the server and frontend related scripts used by users and administrators to access and check the data and process the reported events.